Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fphys.2021.726345
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Growth Differentiation Factor 11 Shortens Telomere Length by Downregulating Telomerase Activity

Abstract: Maintenance of telomere length is essential to delay replicative cellular senescence. It is controversial on whether growth differentiation factor 11 (GDF11) can reverse cellular senescence, and this work aims to establish the causality between GDF11 and the telomere maintenance unequivocally. Using CRISPR/Cas9 technique and a long-term in vitro culture model of cellular senescence, we show here that in vitro genetic deletion of GDF11 causes shortening of telomere length, downregulation of telomeric reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Interestingly, the negative correlation between telomerase and GDF11 is inconsistent with known data. Wang et al found that GDF11 deficiency (in vitro) is associated with telomere shortening and reduced telomerase expression [45]. Similar results are described in the study by Chen et al, who also found that GDF11 enhanced telomerase activity [46].…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, the negative correlation between telomerase and GDF11 is inconsistent with known data. Wang et al found that GDF11 deficiency (in vitro) is associated with telomere shortening and reduced telomerase expression [45]. Similar results are described in the study by Chen et al, who also found that GDF11 enhanced telomerase activity [46].…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, c -MYC promotes hTERT deregulation, resulting in the reduction of telomere length, telomerase activity and cell proliferation [ 82 ]. Additionally, TERT can act as a transcription co-factor that regulates expression of several genes [ 77 ], which are summarized in Supplementary Table S1 [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ,…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Chen et al , mice with ischemia-reperfusion injury overexpressing GDF11 in the myocardium had higher telomerase activity (Chen et al 2021 ). Wang et al showed that the loss of GDF11 significantly downregulated telomerase activity (Wang et al 2021 ). Zhao et al documented the positive effect of telomerase on GDF11 rejuvenation function in patients after myocardial infarction (Zhao et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%